Brick Wall Texture Projection Using Parameters for 3D Game Environments - Eveline Dau Leja (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Texture creation has been one of the important aspects in creating 3D environment. It could support an object that could be identified by the viewer. There has been software that providing the creation of a texture for a playable 3D game asset. The purpose of this research was to find the method of making a wall texture and to show the in-app parameters that could be applied. The objective of this research is to find any possible limitation toward using the software. As a step to make exploration thoroughly, a brick wall design has been made with initial modelling in ZBrush and Maya app. Followed by the usage of Substance 3D Painter as a variable to control the texture modification. There was more in-depth explanation in creating a defined surface texturing with in-app technical parameters.